'A massive multi-faceted screening room': LA Freewaves curates Hollywood boulevard. (22nd June 2012) - Reynolds, Matthew
The 2008 Freewaves festival HollyWould featured the exhibition of 160 artists whose experimental video art, new media works and staged performances took place in storefronts, tattoo parlours, galleries and restaurants along Hollywood boulevard. Festival curators used the five-day event to interrogate Hollywood's 30-year urban revitalization programme – a plan that has dramatically transformed the built landscape and social demographics of the neighborhood. Using Guy Debord's theories of the spectacle and détournement, this article will explore whether HollyWould was an effective attempt to détourn urban renewal itself by reframing the neighborhood's ongoing transformation for viewers, tourists and local residents.